Application of low injection rate and low contrast agent dose in three-dimensional rotational digital subtraction angiography of the intracranial aneurysm. Issue 3 (June 2016) - Gao, Zhimei; Zeng, Yongming; Sun, Jingkun; Yang, Jingjie; Zhou, Yang; Zhou, Mi; Song, Tingni
Objective: The objective of this article is to explore the feasibility of low injection rate and low contrast agent dose in three-dimensional rotational digital subtraction angiography (3D DSA) of the intracranial aneurysm. Materials and methods: Fifty-one patients with suspected intracranial aneurysms were included. The catheter tip was kept within the internal carotid artery at the epistropheus level. Patients were divided into three groups randomly according to injection rate: group A (1.5 ml/s, n  = 18), group B (2.0 ml/s, n  = 18), and group C (3.0 ml/s, n  = 15). The noise, signal-to-noise ratio (SNR), and carrier-to-noise ratio (CNR) of C2, C6, M1, and A1 segments were calculated. The continuous subtraction images and reconstructed images were evaluated by two technicians. Results: No significant differences were found in noise between groups A and B, and groups A and C. Significant differences were found in the SNR and CNR of M1 and A1 segments between groups A and B, and groups B and C, but for C2 and C6 segments, they were not significant. Significant differences were found in the SNR and CNR of all segments between groups A and C. Significant differences were found in the contrast agent dose between all three groups. No significant differences were found in scores evaluated by two physicians between the three groups. Conclusion: The personalized injection protocol of low injection rate and low contrast agent dose in 3D DSA of the intracranial aneurysm is feasible. The application of this protocol can reduce the dose of iodine and obtain satisfactory images.